Effect of Using Building Maintenance Information Management System in Maintenance Process in Ministry of Education - Hussein, Twana Abdullah; Oztas, Ahmet (Kurdistan Journal of Applied Research, 2020)
Educational buildings and Schools are one of the important facilities in community directly related to all families and any problems in the buildings affect the learning process, in Kurdistan according to the latest status about 60% of schools need maintenance and renovations and these data’s needs to manage properly. Information management involves the design of a system in which data is collected and processed into management information, Missing building information or outdated lead to ineffective project management. In this research a web-based model namely BMIMS (Building Maintenance Information Management System) is developed to record, kept, manage and share all information between technical staff in directories. The Model presented to the technical staffs in MOE (Ministry of Education), perform a survey using the special questionaries’ form. The results show that the system has an impact on maintenance process and information management in MOE, the system outcome effect on three themes which are information, communication and cost. The model lead to increase collaboration, communication and productivity, and reducing request for information, losing data, time, rework and administration cost. BMIMS also improves data gathering, information management, better design and construction decisions, knowledge transfer, and staffs technical skills. The research indicates the factors which lead to implement in MOE, training staff is the first one after that the hardware and IT issue after that adoption by top managers. This model is most suitable for other ministries carrying out maintenance.